ChemInform Abstract: Pd‐Catalyzed Reaction of Aryl Halides and Propargyl Furylmethyl Ethers: A Novel Pathway to Functionalized Dihydroisobenzofurans. Issue 3 (21st January 2014) - Chen, Lingzhu; Shen, Ruwei; Wu, Luling; Huang, Xian
Abstract The reaction of propargyl furylmethyl ethers (I) with aryl halides (II) in the presence of copper and palladium catalysts directly leads to desired dihydroisobenzofurans.